Integrated Intelligent Computing, Communication and Security - Krishna, A.N; Srikantaiah, K.C; Naveena, C. (Studies in Computational Intelligence,, 2019)
This book highlights the emerging field of intelligent computing and developing smart systems. It includes chapters discussing the outcome of challenging research related to distributed computing, smart machines and their security related research, and also covers next-generation communication techniques and the networking technologies that have the potential to build the future communication infrastructure. Bringing together computing, communications and other aspects of intelligent and smart computing, it contributes to developing a roadmap for future research on intelligent systems.